Karakteristik Fisik Serbuk Ekstrak Buncis (Pheseolus vulgaris L) dengan Variasi Lama Penyimpanan - Rizki Nugrahani; Yayuk Andayani; Aliefman Hakim (Journal Syifa Sciences and Clinical Research, 2021)
Research has been carried out on the analysis of physic properties of green bean extract powder (Phaseolus vulgaris L). This study aims to determine the physical characteristics of the bean extract powder that has been stored in a predetermined time variation. The physic properties tested included water content, solubility and organoleptic tests. The results of the sample water content test with storage variations of less than 1, 1, 2 and 3 months respectively were 5.55%, 2.86%, 3.83% and 3.54% and the solubility was 42.67%, 33, 84%, 44.51% and 34.33% for Artificial Gastrid Fluid (AGF) solvents and 31.79%, 35.08%, 43.24 and 34.52% for Water solvents. The results of the organoleptic test showed that the color of the bean extract powder sample with a storage time of ± 2 months was the most preferred by the panelists, Fresh samples had the highest average scores for taste and aroma, of the panelist samples preferred the samples that had been stored for ± 3 months